SUPPORTING NOTES 19870325 MEMO TO SDC (Tufts Archival Research Center, 2007)
Handwritten; Supporting notes for memo to SDC, presenting 1987 Professional Fees cost center budget. Includes costs for individual consultants working for TI and affiliated groups. Also includes costs for media relations, legislative, and literature reviews.